Review of the genus Hippodamia (Coleoptera: Coccinellidae) in the Palearctic region. (3rd April 2021) - Biranvand, Amir; Nedvěd, Oldřich; Nattier, Romain; Nepaeva, Elizaveta; Haelewaters, Danny
ABSTRACT: Hippodamia Chevrolat, 1836 currently comprises 19 species. Four species of Hippodamia are native to the Palearctic region: Hippodamia arctica (Schneider, 1792), H. septemmaculata (DeGeer, 1775), H. tredecimpunctata (Linnaeus, 1758), and H. variegata (Goeze, 1777). Here, we provide an identification key to these species, along with illustrations of morphological characters.